The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7848/ksgpc.2015.33.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Tree Height and Canopy Crown from Drone Images Using Segmentation

Abstract: Increasing numbers of studies are being pursued on forests and green spaces to reduce the carbon dioxide levels in the atmosphere, with the aim of mitigating global warming (Lee et al., 2014). However, because a forest area is not easily accessible and has a large number of trees, we need to find an economic and accurate method to acquire tree information such as the heights and the diameters of trees (Chang et al., 2006). Methods for the automatic extraction of the tree area and height can be grouped by sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…In particular, UAV equipped with consumer-grade onboard system camera and different sensors have been used to estimate tree counts, tree heights and crowns measurements due to its low cost and faster performance compared to traditional methods [22,23,[69][70][71][72][73][74]. In this paper, we present a simplified framework for automated ITD from UAV-SfM derived CHM based on algorithms designed for LiDAR data processing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, UAV equipped with consumer-grade onboard system camera and different sensors have been used to estimate tree counts, tree heights and crowns measurements due to its low cost and faster performance compared to traditional methods [22,23,[69][70][71][72][73][74]. In this paper, we present a simplified framework for automated ITD from UAV-SfM derived CHM based on algorithms designed for LiDAR data processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, research in this area is still in its infancy, especially for ITD [70]. Lim et al [23] identified 11 of 13 trees, with one false positive, utilizing stacked RGB ortho-image and CHM segmentation. Trees not identified possessed small canopies which were not clearly defined from neighboring trees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations